Technical ceramics from a forge? A pottery find from Călugăreni/Mikháza (Romania) - Fiedler, Manuel; Höpken, Constanze; Oberhofer, Karl (Rei Cretariae Romanae Fautorum Acta, 2023)
In Călugăreni/Mikháza (RO) excavations are taking place for several years, which include several sites: the military fortress and the vicus with a bath. In the vicus next to the Roman fortress was found a ceramic vessel which was destroyed on site. It is an unusual vessel that ends in a wide tube and can be interpreted as part of a technical installation. Finds in the vicinity indicate that there may have been a forge and the vessel could have been part of a construction ventilating the Blacksmith's fireplace. The vessel itself could have been used as a bellows or a wind hole under the fire.